Cr(VI) adsorption on low-cost activated carbon developed from grape marc-vinasse mixture - Arslanoglu, Hasan; Kaya, Semih; Tumen, Fikret (Taylor & Francis Inc, 2020)
In the present work, an activated carbon obtained as by-product in a fertilizer preparation process was studied for Cr(VI) adsorption from aqueous solutions. Batch adsorption experiments were carried out by varying the pH, initial Cr(VI) concentration, contact time, activated carbon dosage and temperature. The adsorption of Cr(VI) was found to be highly pH-dependent and maximum adsorption was observed in the acidic pH range. Equilibrium data were applied to Langmuir, Freundlich, and D-R adsorption isotherms. Also, kinetic data were analyzed for pseudo-first, pseudo-second, and intraparticle diffusion models. Langmuir adsorption isotherm and pseudosecond kinetic model were fit best to the related data. Maximum adsorption capacity was found to be 74.63mg/g at the conditions of the temperature of 25 degrees C, the pH of 3.5, the contact time of 360 min and the adsorbent dosage of 1 g/L. Activation energy, mean adsorption energy (from D-R isotherm) and thermodynamic parameters were evaluated and nature of the adsorption process was found to be as physical, endothermic, and spontaneous.
Keywords: Activated carbon; vinasse-grape marc mixture; Cr(VI) adsorption; isotherm; kinetics; thermodynamic parameters